Effectiveness of a structured AETCOM training intervention on knowledge, attitude and communication practices among medical interns in Maharashtra: an interventional study - Pawde, Preeti; Solanke, Prashant; Dhage, Satishkumar (International Journal of Research in Medical Sciences, 2026)
Background: Attitude, ethics and communication are key attributes in doctor-patient relationship and to strengthen them, National Medical Commission (NMC) introduced the Attitude, Ethics and Communication (AETCOM) module within Competency-Based Medical Education (CBME). Evidence on its impact among medical interns in Maharashtra is limited. This study evaluates interns’ baseline knowledge, attitudes and communication practices regarding AETCOM and examines the module’s effectiveness in improving them. Methods: An interventional study was conducted among 180 medical interns from three medical colleges in Maharashtra from December 2025 to May 2026. Baseline assessment was carried out using a validated Knowledge-Attitude-Practice (KAP) questionnaire and Kalamazoo Essential Elements Communication Checklist–Adapted (KEECC-A). A structured 12-hour AETCOM training was delivered over four weeks, with post-intervention evaluation done six weeks later. The difference in means of pre-intervention and post-intervention scores were analysed for statistical significance using ‘paired t-test’(‘p’ value<0.05 considered significant). Results: The mean knowledge score increased significantly from 18.6±4.2 to 27.9±3.1 (p<0.001). Mean attitude score improved from 62.4±8.7 to 79.6±6.4 (p<0.001). Mean communication practice score increased from 58.3±10.2 to 91.4±12.1 (p<0.001). Female interns demonstrated marginally higher post-test scores than males, though the difference was not statistically significant (p>0.05). Conclusions: The structured AETCOM module demonstrated significant effectiveness in improving knowledge, professional attitude and communication practices among medical interns in Maharashtra.